Sport Financing Through the Gambling Revenues in Montenegro - Suncica Rogic; Milena Radonjic; Vladimir Djurisic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Sport fi nancing is of great national importance, having in mind that it's recognized as an activity of public interest by the Law. Since most of sport organizations in Montenegro are publicly owned, they are dependent on public fi nancing, which are often scarce and insuffi cient for fulfi lling sport's function in society. Therefore, new sources of fi nancing must be introduced. One of the most common funding systems in Europe includes resources redirected from gambling industry profi ts - taxed by the government. Even though the idea isn't exactly new, it's implemented diff erently in various countries. This paper analyzes current Montenegrin system of sport fi nancing from this source, compares it to other European countries and provides recommendations for its' improvement. Taking into account that most gambling revenues come from sport betting, it would be benefi cial for the society that most of these incomes fi nd their way back to sport. The research results for Montenegro show considerable lagging behind other European countries in terms of sport funding from taxed gambling profi ts. With the share of only 14% of funds allocated to sport from this source there is a plenty of room for Montenegro to improve its sport fi nancing system, which would lead to faster sport development. This share is considerably low, compared to neighboring EU countries such as Croatia's 35% and Slovenia's 80%. With certain improvements and taking into account other countries good practice examples, Montenegrin sport fi nancing system can be considerably improved.